Information Management Behaviour of Dairy Farmers in Cuddalore District of Tamil Nadu - Gopi, R.; Sindhu, M. G.; Thilakar, P.; Manivannan, A.; P. Mathialagan (International Journal of Livestock Research, 2018)
The present study was undertaken to critically analyze the Information management behaviour of dairy farmers in Cuddalore district of Tamil Nadu. The data were collected from five villages of Mangalur block comprising of 60 respondents through structured interview schedule. The results revealed that Veterinarians were the major personal cosmopolite source of information. Family members and progressive farmers were the most preferred personal localite sources of dairy information on improved farm practices. Television was the most preferred impersonal cosmopolite source of dairy farming information. Dairy farmers discuss their ideas with family members to evaluate the information and try to memorize for further use in transfer of technologies in their farm situation. Efforts should be made to educate the farmers to participate in training, field days, field trip, exhibition for increasing awareness and knowledge and better understanding of technologies.